Triple method approach to development of a genre-based approach to teaching ESL/EFL writing: a systematic literature review by bibliometric, content, and scientometric analyses - Zhai, Xiuwen; Razali, Abu Bakar (SAGE Publications, 2023)
In the last 19 years (2003–2021), research on genre-based approaches (GBAs) to writing pedagogy has been accumulating in the fields of English as a second language (ESL) and English as a foreign language (EFL). This review mapped existing literature to identify research trends and provide a research agenda for future GBAs. This study employed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and identified 52 published articles and 2 unpublished doctoral theses via a structured keyword search on Web of Science, Scopus, ERIC, Google Scholar, and ProQuest in the fields of teaching English to speakers of other languages, language learning, and education. The results show that GBA is now widely used in teaching English academic writing to ESL/EFL tertiary/graduate students. The main research findings include: (1) the top five countries in the number of paper publications are China (i.e., five), the United States (i.e., five), Japan (e.g., 4), Thailand (e.g., four), and Sweden (e.g., four); (2) the top four authors in the number of paper publications are Hyland (i.e., two), Lu (i.e., two), Negretti (i.e., two), and Pineh (i.e., two); and (3) the top three most strengthen keywords are writing pedagogy, genre-based approach, and English for academic purpose. This study also discusses the theoretical and practical implications.